The Effect Of Reality Group Counseling With The Wdep Technique In Increasing Adolesceny Social Responsibility - Sulistiyowati, Linda; Tawil, T; Yuhenita, Nofi Nur (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of group counseling techniques WDEP towards increasing the social responsibility of youth in Sokorini Village, Muntilan, Magelang. In this research is a type of research Pre-experiment by using design One Group Pretest Posttest Design. The design uses one group of subjects with one type of treatment, namely the experimental group. The population in this study were Sokorini teenagers, which consisted of 15 teenagers. The number of samples in this study were 7 teenagers who had a score ofpretest low and medium categories. Determination of sampling using analysis purposive sampling, namely the determination based on the goals or characteristics that have been determined. The analytical method in this study uses parametricPaired sample t-test The results of this study indicate that technical group counseling WDEP positive effect on increasing adolescent social responsibility. This is evidenced by the test resultspaired sample t-test with a significant 2-tiled 0.001<0,05. And based on the results of the analysis and discussion, there is a difference in the average score of the adolescent social responsibility questionnaire of 29.02% from the resultspretest and result posttest youth social responsibility questionnaire.